Physical comparison between Rampasasa Pygmy and Yogyakarta children of Indonesia - Neni Trilusiana Rahmawati; Janatin Hastuti; Rusyad Adi Suriyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACTIn growth studies, somatotyping allows one to characterize changes in physique during growth in order to monitor growth patterns and to better understand variations in adult physique. Information on the physique of children with short stature is limited In Indonesia the study of somatotype for Pygmy children had never been done. The aims of this study were to compare the physiques of Rampasasa Pygmy and Yogyakarta children and to evaluate factors that might lead to variability in physiques. The sample consisted of 61 Rampasasa Pygmy (32 boys and 29 girls) and 319 Javanese children in Yogyakarta (173 boys and 146 girls) aged 8–13 years. Height, weight, biepicondylar breadths of the humerus and femur, calf and upper arm circumferences, and skinfolds (at triceps, subscapula, calf, and supraspine) were measured on each subject. We used somatotyped by the Heath-Carter method. The results showed that the Pygmy children were shorter, lighter, and less endomorphic than the Yogyakarta children. Our findings suggest that the observed differences between Rampasasa Pygmy and Yogyakarta children could be related mainly to environment background in the two areas.